Effect of sintering temperature on microstructure and magnetic and dielectric properties of M-type barium ferrites. Issue 19 (1st October 2022) - Wang, Xueying; Zhang, Huaiwu; Li, Jie; Liu, Kui; Jin, Lichuan; Cheng, Liu; Jia, Lijun; Liao, Yulong; Zhang, Dainan
Abstract: In this study, the effect of sintering temperature on microstructure, magnetic properties and dielectric behavior of M-type barium ferrites (BaM) is systematically analyzed. BaBi0.45 (CoTi)1.2 Fe9.15 O19 samples with a dense microstructure and typical hexagonal shape are obtained at the sintering temperature of 920 °C. Moreover, the permittivity (ε′) of BaM increases to 21.41 at 0.01 GHz and the permeability ( μ ′) increases to 10.82 at the optimized temperature of 920 °C. Based on mathematical fitting, the saturation magnetization ( 4πM s ) of samples is calculated to be 3272.27 Gauss and the magnetocrystalline anisotropy constant K 1 is found to be 4.18 × 10 6 erg cm −3 . More interestingly, the magnetic loss angle tangent (tan δ μ ) is reduced to 2.7 × 10 −1 and the dielectric loss angle tangent (tan δ ε ) is reduced to 5.8 × 10 −3 . The optimized magnetic and dielectric properties, with low losses, enhance the suitability of BaM ferrites for miniaturized microstrip devices.